Factors Affecting Return on Assets at Bank Muamalat Indonesia in 2012-2021 - Febriyanti, Ajeng; Rendra Erdkhadifa (HM Publisher, 2022)
Bank Muamalat has significantly decreased managerial profitability in the last six years compared to other Sharia Commercial Banks. Bank Muamalat of Indonesia experienced a decline in profitability that has no growth and continues to be restructured. Meanwhile, profitability is one of the benchmarks for the success of Sharia banking in managing its financial performance. The present study aims to analyze the simultaneous and partial effect of variables NPF, BOPO, CAR, FDR, and TPF on the ROA of Bank Muamalat of Indonesia. This study implements a quantitative method using quarterly data from Bank Mumalat of Indonesia for the period 2012-2021. The technique used to analyze the data were the multicollinearity test, multiple regression analysis tests, and classical assumption test. The results of this study indicate that there is a simultaneous influence between the variables NPF, BOPO, CAR, FDR, and TPF to ROA. NPF shows a positive and significant value to Bank Muamalat's ROA. BOPO has a negative and significant effect on the ROA of Bank Muamalat. Furthermore, CAR has a positive and significant effect on Bank Muamalat's ROA. FDR has a positive and significant effect on ROA. FDR in this study has the greatest influence over other variables with a t-count value of 3.922, which is smaller than t-table 2.030. While TPF in this study has no significant effect on the ROA of Bank Muamalat.